Risk Assessment for Longitudinal Trajectories of Modifiable Lifestyle Factors on Chronic Kidney Disease Burden in China: A Population-based Study - Ping Li; Mingjia Yang; Dong Hang; Yongyue Wei; Hongling Di; Hongbing Shen; Zhihong Liu (Journal of Epidemiology, 2022)
Background: Chronic kidney disease (CKD) is an important contributor to morbidity and mortality from noncommunicable diseases. We aimed to examine the longitudinal trajectories in risk factors, estimate their impact on CKD burden in China from 1991 to 2011, and project trends in the next 20 years. Methods: We used data from a cohort of the China Health and Nutrition Survey and applied the comparative risk assessment method to estimate the number of CKD events attributable to all non-optimal levels of each risk factors. Results: In 2011, current smoking was the leading individual attributable factor for CKD burden in China responsible for 7.9 (95% confidence interval [CI], 7.5–8.3) million CKD cases with a population-attributable fraction of 8.7% (95% CI, 6.0–11.6), while the rates of smoking have reduced and may have mitigated the increase in CKD. High triglyceride (TG) and high systolic blood pressure (SBP) were the leading metabolic risk factors responsible for 6.8 (95% CI, 6.4–7.1) million and 5.8 (95% CI, 5.5–6.1) million CKD-attributable cases, respectively. Additionally, the number of CKD cases associated with high body mass index (BMI), high diastolic blood pressure (DBP), high plasma glucose, and low high-density lipoprotein cholesterol (HDL-C) was 5.4 (95% CI, 5.1–5.6), 3.9 (95% CI, 3.7–4.1), 3.0 (95% CI, 2.8–3.1) and 2.6 (95% CI, 2.5–2.8) million, respectively. Conclusion: Current smoking, high TG, and high SBP were the top three risk factors that contributed to CKD burden in China. Increased BMI, DBP, plasma glucose, and decreased HDL-C were also associated with the increase in CKD burden.